2005
DOI: 10.1177/096739110501300107
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity of Needle Punched Preforms made of Carbon and OxiPAN Fibres

Abstract: The thermal conductivity of preforms made by a needle punching technique has been measured using a tailor-made apparatus. Measurements were carried out in the absence of the matrix resin to find the thermal conductivity of the preforms themselves. The preforms were made with a variety of material compositions and textile structures, and various needle punching densities. Preforms made of woven fabric showed higher thermal conductivity than preforms of felt fabric. Needle punching density had a strong influence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
(15 reference statements)
1
1
0
Order By: Relevance
“…These results correlate well with the results obtained by µCT analysis. A similar effect has been observed in previous studies [ 64 , 65 , 66 ], which confirmed the influence of needle-punching density on thermal conductivity by producing a series of CFs with different needle-punching densities. Therefore, the combined effects of the conductive nature and orientation of the carbon fibers influences the anisotropic heat transfer behavior.…”
Section: Resultssupporting
confidence: 91%
“…These results correlate well with the results obtained by µCT analysis. A similar effect has been observed in previous studies [ 64 , 65 , 66 ], which confirmed the influence of needle-punching density on thermal conductivity by producing a series of CFs with different needle-punching densities. Therefore, the combined effects of the conductive nature and orientation of the carbon fibers influences the anisotropic heat transfer behavior.…”
Section: Resultssupporting
confidence: 91%
“…The barbs on the needles hook some fibers in the layered materials and insert them vertically in descending motion. These third direction fibers provide a reinforcing effect between the layers and improved the delaminating behavior of the bi-directional composites [22][23][24]. These preforms are suitable for producing small and complex composite parts.…”
Section: Needle-punch Preformmentioning
confidence: 99%